2007
DOI: 10.1074/jbc.m606865200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Melanocortin 1 Receptor Signaling and Trafficking by Thr-308 and Ser-316 and Its Alteration in Variant Alleles Associated with Red Hair and Skin Cancer

Abstract: The melanocortin 1 receptor (MC1R), a G protein-coupled receptor (GPCR) positively coupled to adenylyl cyclase, is a key regulator of melanocyte proliferation and differentiation and a determinant of pigmentation, skin phototype, and skin cancer risk. MC1R activation stimulates melanogenesis and increases the ratio of black, strongly photoprotective eumelanins to yellowish and poorly photoprotective pheomelanin pigments. Desensitization and internalization are key regulatory mechanisms of GPCR signaling. Agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 48 publications
(73 reference statements)
2
76
0
2
Order By: Relevance
“…On the other hand, ARRB1 had no inhibitory effect. MC1R internalization was next assessed by an acid-wash method that discriminates external from internal (acid-wash resistant) agonist-receptor complexes (Herraiz et al, 2011b;Sánchez-Laorden et al, 2007). In line with equilibrium binding data, ARRB2 isoforms increased MC1R internalization in the presence of agonist, whereas ARRB1 had no effect (Fig.…”
Section: Arrb Expression In Human Melanocytic Cellsmentioning
confidence: 59%
See 1 more Smart Citation
“…On the other hand, ARRB1 had no inhibitory effect. MC1R internalization was next assessed by an acid-wash method that discriminates external from internal (acid-wash resistant) agonist-receptor complexes (Herraiz et al, 2011b;Sánchez-Laorden et al, 2007). In line with equilibrium binding data, ARRB2 isoforms increased MC1R internalization in the presence of agonist, whereas ARRB1 had no effect (Fig.…”
Section: Arrb Expression In Human Melanocytic Cellsmentioning
confidence: 59%
“…We have previously shown that human MC1R desensitization is mediated by GRK2-or GRK6-dependent phosphorylation of amino acid residues T308 and S316 located in the C-terminal extension, and that MC1R is endocytosed following agonist binding (Sánchez-Laorden et al, 2007;Sánchez-Más et al, 2005a). However, the role of nonvisual ARRB isoforms in regulating MC1R signaling remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were centrifuged (105,000 ϫ g, 30 min) and a volume of supernatant containing 10 g of protein was mixed (2:1 ratio) with sample buffer (180 mM Tris-HCl, pH 6.8, 15% glycerol, 9% SDS, 0.075% bromphenol blue, and 7.5% ␤-mercaptoethanol). Electrophoresis and Western blotting were performed as described (28,29). Comparable loading was ascertained by stripping and reprobing the membranes with an anti-ERK2 antibody.…”
Section: Materials-[mentioning
confidence: 99%
“…We next compared agonist-induced internalization. We used an acid wash protocol that distinguishes acid-sensitive radiolabeled agonist bound to the MC1R at the cell surface from acid wash-resistant internalized ligand (29). Only minor differences in the internalization rate were detected for WT or K0-MC1R, in the presence or absence of MGRN1s (Fig.…”
Section: Inhibition Of Mcr Signaling By the Mgrns Is Independent On Rmentioning
confidence: 99%
“…A functional impairment in MC1R signalling alters the downstream pigmentation pathways, causing an accumulation of pheomelanin that, in turn, has reduced UV protective capacity and can produce cytotoxic and mutagenic metabolites (Sturm, 1998), accelerating melanocytic transformation. This functional impairment can result from different mechanisms: some variants fail in the stimulation of cAMP production (Beaumont et al, 2007;Garcia-Borron et al, 2005), while others show MC1R reduced affinity for its ligand -MSH (Ringholm et al, 2004) or there are even defects in desensitization and internalization of the MC1R receptor itself (Sanchez-Laorden et al, 2007). Given the role of MC1R on epidermal response to UV-induced damage, it is not surprising that the MC1R allelic state influences melanoma risk, by directly regulating skin pigmentation.…”
Section: Mc1rmentioning
confidence: 99%